Digital Infrastructure Development For Palm Oil Plantation 4.0 - Muhamad Iqbal (Journal of Cyber Health and Computer, 2024)
The implementation of digital infrastructure in palm oil plantations aims to enhance productivity, sustainability, and efficiency through the integration of advanced technologies. This paper explores the necessary equipment and technologies for realizing the concept of Palm Oil Plantation 4.0, including IoT devices, automation systems, data analytics platforms, and communication networks. The study outlines the benefits, challenges, and potential impacts on the industry.